Efektivitas Ekstrak Daun Bintaro (Cerbera odollam gaertn.) Untuk Pengendalian Hama Utama Pada Tanaman Cabai (Capsicum annum Linn.) - Winarni, Arwidya; Pramudi, Muhammad Indar; Liestiany, Elly (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
The use of botanical pesticides from natural ingredients that can be utilized is the bintaro plant (Cerbera odollam Gaertn.). This research aims to determine the effectiveness of bintaro leaf extract with water and ethanol as a solvent in controlling the main pests on chili plants. This research was conducted using the Completely Randomized Design (CRD) method. The results of the research showed that the application of the botanical pesticide Bintaro leaves was able to reduce pest damage to chilies, the lowest intensity of leaf damage was seen in the PD treatment (5.99%), then the lowest percentage of fruit damage was observed in the KC treatment (11.37%) and the PC (14.94%). Apart from that, the application of the botanical pesticide Bintaro PA leaves produced the number of fruit (47,146 fruit/ha), the second largest after chemical control (49,923 fruit/ha).